Bisphenol A Exposure in Exclusively Breastfed Infants and Lactating Women: An Observational Cross-sectional Study - Seda Çiftçi; Sıddıka Songül Yalçın; Gülhan Samur (Galenos Yayincilik, 2021)
Objective:Bisphenol A (BPA) is a known endocrine disruptor and free BPA will interact with estrogen. BPA is also fat soluble and will therefore contaminate breast milk. The European Food Safety Authority has set a limit for temporary tolerable daily intake of 4 μg/kg body weight/day in breastfeeding infants. The aim of this study was to measure human milk BPA concentrations in Turkish women and thus exclusively breastfed infants' exposure to BPA.Methods:Healthy, postnatal, exclusively breastfeeding women were recruited and breast milk samples were collected. Free BPA concentration was analyzed in the milk samples using competitive enzyme-linked immunosorbent assay. Participants' demographic characteristics and nutritional habits were investigated through face-to-face interviews using a detailed questionnaire.Results:Eighty women participated. Median milk free BPA level was 0.63 μg/L. There was no statistically significant association between maternal body mass index, birth type, parity, infant birth week, infant birth weight, and human milk BPA concentration. Nevertheless, there was a significant association between human milk BPA level and consumption of fast-food and carbonated drinks (p=0.022 and p=0.018, respectively). Exclusively breastfed infants' mean BPA exposure was 0.0099±0.0079 μg/kg bw/day. There was a moderate negative significant correlation between infant BPA exposure and infant current body weight (r=0.327, p=0.003).Conclusion:BPA exposure in exclusively breastfed infants was within accepted limits and the current dietary exposure level of infants in this cohort was safe.